Evaluation of blood flow in arteritic anterior ischemic optic neuropathy using laser speckle flowgraphy: A case series - Chiaki Yamaguchi; Naoki Kiyota; Noriko Himori; Takahiro Oshima; Takayuki Takeshita; Kazuko Omodaka; Satoru Tsuda; Toru Nakazawa (American Journal of Ophthalmology Case Reports)
Background: Arteritic anterior ischemic optic neuropathy (AAION), primarily caused by giant cell arteritis, is a leading cause of blindness. This disease results in significant ocular blood flow (BF) impairment, though data on ocular hemodynamics are limited. Methods: This observational case series enrolled four patients treated for AAION (age: 81.8 ± 7.8 years; male to female ratio: 3:1) who underwent laser speckle flowgraphy (LSFG) scanning at the initial visit and after steroid treatment in both eyes. Mean blur rate (MBR), an LSFG parameter that represents BF velocity, was obtained in the optic nerve head vessel area (ONH-MV), ONH tissue area (ONH-MT), and peripapillary choroid, in addition to common ophthalmologic parameters. Results: At the initial visit, all affected eyes had no light perception in best-corrected visual acuity (BCVA) testing, and three cases had a severe increase in circumpapillary retinal nerve fiber layer thickness (cpRNFLT; 191.00 ± 42.03 μm). Pre-treatment, all affected eyes showed decreases in ONH-MV, ONH-MT, and choroidal MBR; this improved after steroid treatment by 80.3 ± 107.6 %, 39.1 ± 79.7 %, and 289.4 ± 303.4 %, respectively. Pre-treatment, all fellow eyes showed no impairment in BCVA or changes in the cpRNFLT. Post-treatment, two fellow eyes showed an increase in ONH-MV and ONH-MT parameters (72.8 ± 32.6 % and 82.2 ± 22.3 %, respectively), while all fellow eyes showed an increase in choroidal MBR (152.7 ± 126.1 %). Conclusion: LSFG could be useful for monitoring ocular BF changes in eyes with AAION and asymptomatic fellow eyes before and after steroid treatment.